Case report and literature review: novel TXNRD2 compound heterozygous variants in familial glucocorticoid deficiency type 5 - Xiaoyan Wang; Xiuli Chen; Ting Chen; Rongrong Xie; Qi Lin Chen; Haiying Wu; Fengyun Wang (Frontiers in Pediatrics)
Familial glucocorticoid deficiency (FGD) is a rare autosomal recessive disorder characterized by isolated glucocorticoid deficiency. Mutations of MC2R, MRAP, STAR, NNT, and TXNRD2 have been implicated in FGD pathogenesis. To date, only four families with TXNRD2-associated familial Glucocorticoid Deficiency Type 5 (FGD5) have been reported worldwide. We report a patient with clinical features consistent with FGD5, increasing the total number of reported cases. Including this case, 11 probands across five independent kindreds have now been identified globally. Functional studies demonstrated that the novel compound heterozygous variants (c.1391A > G; p.H464R and c.1141C > T; p.R381W) reduce TXNRD2 protein levels in a heterologous expression system. This case expands the genetic spectrum of FGD5 and suggests a potential association between TXNRD2 variants and electrocardiographic abnormalities. Our findings underscore the importance of TXNRD2 in adrenal redox homeostasis and provide new insights for FGD5 diagnosis.